Desafios da expansão urbana em áreas ambientalmente frágeis : o entorno da Rodovia Darly Santos, Vila Velha-ES - Garcia, Daniele Goldner (2013)
This work consists in the analysis of the urban expansion processes on environmental fragile areas with the aim of considering the feasibility of the adequacy of urban planning for this condition. The importance of this approach is justified by the high f